State sponsors of terrorism disclosure and SEC financial reporting oversight - Hills, Robert; Kubic, Matthew; Mayew, William J. (Journal of Accounting and Economics, 2021)
We examine whether SEC effort to review state sponsors of terrorism (SST) disclosure negatively influences financial reporting oversight. Using comment letter inquiries about SST to measure effort, we find the likelihood that the SEC fails to identify a financial reporting error increases when comment letters reference SST. Consistent with SST disclosure review crowding out financial reporting oversight, comment letters referencing SST are less likely to mention accounting, non-GAAP, and MD\ &A issues. These effects are unique to SST as we find comment letter references to non-SST issues complement financial reporting oversight. Data obtained through a Freedom of Information Act request reveals a temporal shift in the occupational mix of SEC reviewers towards (away from) lawyers (accountants) that coincides with an increased focus on SST. Path analysis reveals that accountants (lawyers) are more (less) likely to detect errors and comment on financial reporting topics, with an indirect path through SST exacerbating these effects.